2015
DOI: 10.3329/ralf.v1i1.22357
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of reproductive diseases and its associated risk factors in crossbred dairy cows

Abstract: Reproductive diseases of crossbred dairy cows significantly reduce productivity which is of great concern of dairy producers worldwide. The objectives of this study were to determine the prevalence of reproductive diseases and its associated risk factors in crossbred dairy cows in selected areas of Bangladesh. The study was conducted at eight villages of Ullapara Upazila under Sirajganj district. A total of 197 dairy farms having 488 breedable crossbred dairy cows (395 cows + 93 heifers) were randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
5
1
2
Order By: Relevance
“…It is suggested that in order to combat the occurrence of reproductive disorders in cows crossbreeding program through artificial insemination (AI) should be done proper hygienic management. About 2.4% vaginal prolapse were observed which agrees with the findings of 2.2% and 2.7% reported by Sarder et al (2010) and Alam et al (2014), respectively. The prevalence of uterine prolapse was 1.4% in current study which is fairly agree with the findings of 1.3%, 1.4% and 1.6% obtained by Kader (2010), Sarder et al (2010) and Alam et al (2014).…”
Section: Reproductive Disorders Of Dairy Cows In Rajshahi District Ofsupporting
confidence: 90%
See 3 more Smart Citations
“…It is suggested that in order to combat the occurrence of reproductive disorders in cows crossbreeding program through artificial insemination (AI) should be done proper hygienic management. About 2.4% vaginal prolapse were observed which agrees with the findings of 2.2% and 2.7% reported by Sarder et al (2010) and Alam et al (2014), respectively. The prevalence of uterine prolapse was 1.4% in current study which is fairly agree with the findings of 1.3%, 1.4% and 1.6% obtained by Kader (2010), Sarder et al (2010) and Alam et al (2014).…”
Section: Reproductive Disorders Of Dairy Cows In Rajshahi District Ofsupporting
confidence: 90%
“…About 2.4% vaginal prolapse were observed which agrees with the findings of 2.2% and 2.7% reported by Sarder et al (2010) and Alam et al (2014), respectively. The prevalence of uterine prolapse was 1.4% in current study which is fairly agree with the findings of 1.3%, 1.4% and 1.6% obtained by Kader (2010), Sarder et al (2010) and Alam et al (2014). The lower prevalence rate of vaginal and uterine prolapse may be attributed to the available of calcium supply with feed and less chance to occurred hypocalcaemia.…”
Section: Reproductive Disorders Of Dairy Cows In Rajshahi District Ofsupporting
confidence: 90%
See 2 more Smart Citations
“…There was a significant (P=0.01) variation observed in relation to the effect of mastitis on CI ( Table 4). The present study described the number of SPC was 4 which was comparatively higher in cows in which sub-clinical mastitis was converted to clinical, as described by Alam et al (2014).…”
Section: Discussionmentioning
confidence: 51%